Early (Day 15 Post Diagnosis) Peripheral Blood Assessment of Measurable Residual Disease in Flow Cytometry is a Strong Predictor of Outcome in Childhood B‐Lineage Lymphoblastic Leukemia. Issue 2 (7th February 2019) - Loosveld, Marie; Nivaggioni, Vanessa; Arnoux, Isabelle; Bernot, Denis; Michel, Gérard; Béné, Marie C.; Eveillard, Marion
Abstract : Background: In children with acute lymphoblastic leukemia (ALL) low levels of minimal residual disease (MRD) after induction, essentially assessed in the bone marrow, have been shown to be of good prognosis. However, only few studies have tested the peripheral blood for MRD. Methods: Here, we report the impact on survival of peripheral blood (PB) MRD assessment by multiparameter flow cytometry (MFC) at early time points of treatment in 125 B‐ALL children, compared to Day 35 molecular bone marrow (BM) MRD. Patients were sampled for MFC one week postdiagnosis after a pre‐phase of corticotherapy (Day 8), then after one week of chemotherapy (Day 15). The study enrolled 67 boys and 58 girls with a median follow‐up of 52 months. Over the duration of the study, 20 patients relapsed and eight died. MFC was performed based on the leukemia‐associated immunophenotype at diagnosis, using panels of 10 antibodies. Results: Although, PB MFC‐MRD had no prognostic impact at Day 8, Day 15 MRD negativity was associated with a significantly better 4 years DFS (91.6 ± 3% vs. 67.6 ± 9% P = 0.0013). Furthermore, while MFC and molecular data were concordant in most cases, patients with detectable PB MRD on Day 15, yet negative in BM on Day 35 had a significantly lower DFS ( P < 0.0001). Conclusion: This study demonstrates that the less invasive procedure of MFC‐MRD assessment in PB can be informative for childhood ALL patients at the early point of Day 15 of the treatment schedule. © 2019 International Clinical Cytometry Society